Analisis Hukum Islam terhadap Penetapan Hukum Hakim tentang Perkawinan Beda Agama di Indonesia dalam putusan Nomor: 12/Pdt.P/2022/PN. Ptk - Aksa, Fauzah Nur; Hamdani, Hamdani; Nur, Muhammad Tahmid; Fadhia, Amira (LP2M IAIN Palopo, 2024)
This research focuses on analyzing the legal of islam basis of the judge's considerations in Court Determination Number: 12/Pdt.P/2022/Pn. Ptk, and the legality of interfaith marriages are reviewed from Law Number 1 of 1974 concerning marriage, as well as the law regarding court decisions regarding interfaith marriages. The type of research used is qualitative research. This research uses primary and secondary data. The data collection method in this research uses library research. Based on research conducted, it is known that the judge referred to Article 35 of Law number 23 of 2006 concerning Population Administration which states that marriage registration applies to marriages determined by the court, so that the judge interprets the meaning of the marriage determined by the court to be an interfaith marriage. Law Number 1 of 1974 concerning Marriage states that marriage is valid based on the rules of religious law, but if an interfaith marriage is carried out outside the jurisdiction of Indonesia and its registration is considered valid. The legal implications that arise as a result of this court decision are the status and position of children. It is recommended that judges in taking considerations not only refer to one interpretation, but also look at other legal considerations such as the Constitutional Court decision Number 68/PUU-XII/2014 in the petition for Review of Law Number 1 of 1974 concerning Marriage which clearly rejects be firm regarding interfaith marriages, and use considerations based on other laws. To the DPR and the Government to immediately revise the Marriage Law by strengthening the prohibition on interfaith marriages in order to eliminate the legal vacuum. To society, interfaith marriages should not be carried out.